2021
DOI: 10.1177/20503121211039099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics and predicting risk factors of adverse drug reactions among hospitalized older adults: A systematic review and meta-analysis

Abstract: Background: Occurrence of adverse drug reactions is a major global health problem mostly affecting older adults. Identifying the magnitude and predictors of adverse drug reactions is crucial to developing strategies to mitigate the burden of adverse drug reactions. This study’s objectives were to estimate and compare the prevalences of adverse drug reactions, to characterize them and to identify the predictors among hospitalized older adults. Methods: A comprehensive systematic literature search including both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…Systematic reviews that involved hospitalized older patients across the globe reported ADR prevalences of 11.5–24%. 12–15 A study conducted in the US and another from Ethiopia as well as a systematic review that included many studies across the world showed that about 10% of hospital admissions worldwide are related to ADRs. 16–18 In the US, approximately 100,000 emergency hospital admissions of older adults were attributed to ADRs every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews that involved hospitalized older patients across the globe reported ADR prevalences of 11.5–24%. 12–15 A study conducted in the US and another from Ethiopia as well as a systematic review that included many studies across the world showed that about 10% of hospital admissions worldwide are related to ADRs. 16–18 In the US, approximately 100,000 emergency hospital admissions of older adults were attributed to ADRs every year.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study in Uganda reported up to half of the general adults experienced ADRs during hospitalization. 40 However, evidence of ADR prevalence and incidence specifically among the elderly inpatient population in low- and middle-income countries 12 including Uganda, more so from prospective cohort studies, is lacking. We, therefore, conducted a study among elderly inpatients at Medical, Oncology, and Surgical Departments at Mbarara Regional Referral Hospital to determine the prevalence and incidence of suspected ADRs.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the systematic review were published elsewhere. 5 Then we included the 15 previously reported risk factors and four more relevant independent variables, as independent variables in our derivational study conducted at MRRH from November 9, 2020 to May 7, 2021. This study, particularly, aimed at determining the risk factors of hospital-acquired ADRs in this group of patients.…”
Section: Methodsmentioning
confidence: 99%
“…The authors conducted a systematic review on predictors of ADRs in hospitalized older adults and the results are published elsewhere [ 4 ]. We included 15 predictors reported by previous studies as independent variables in our observational study.…”
Section: Methodsmentioning
confidence: 99%
“…The latest systematic review reported a prevalence of ADRs of 22% among hospitalized older adults; 19% for high-income countries and 29% for low-income countries [ 4 ]. In the UK, between 2007/8 and 2014/15, the emergency admissions due to ADRs increased by 53.4%, and the number of bed days that were used due to ADRs also increased by 51.5% over the same period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%